Rhythms of resistance: chants that propelled Zimbabwe's Third Chimurenga - Nyawo, Vongai Z. (Routledge, 2016)
Songs, musical composition with words, have been sung from time immemorial in different cultures for various reasons. They have been composed for a multi-faceted purpose including celebration, expressing sorrow, as a cultural weapon and for pastime. Songs that have been composed and sung to express political sentiments during war times or times of affliction have, in the same breath, shaped and influenced our history. World War 2 was the first major global conflict to take place in the age of electronically mass distributed music, giving an insight into how songs could be used in periods of the most profound hardships and crisis. By the same token, the Zimbabwean society has used songs, among other things, to galvanize and win their wars, from the first to the third Chimurenga. This paper sets out to describe and analyse how songs have become a sure weapon for Zimbabweans in crisis and, in particular, during the Third Chimurenga. Through desk top and interviews, this research wishes to analyse the Third Chimurenga (Hondo Yeminda) showing a growing connection between song and protest and how song becomes synonymous with victory in the eyes of Zimbabweans. The study also, discusses the contents of the songs to establish their connection with the aims and objectives or central concerns of the liberation war.